PENINGKATAN KINERJA BISNIS MELALUI STRATEGI PEMASARAN BERBASIS ONLINE PADA UKM PRODUK CAMILAN TRADISIONAL - Suryandari ISTIQOMAH; Yeni FAJARYANTI; Amina Sukma DEWI (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2020)
The internet is one of the technologies that is inevitable in today's digital era. One effect of the internet is also having an impact on the business world, among others, with the development of e-commerce and the decreasing number of offline retailers. therefore the use of internet / e-commerce as an alternative sale must be made by all entrepreneurs including traditional snack entrepreneurs. This research aims to be able to help SMEs to introduce products through sales through the internet and its derivatives. In addition, this service also aims to introduce traditional snack products with better marketing strategies, including by using more eye catching packaging and selling so that they can be easily accepted by millennials. This research has carried out several activities including operational training in marketing training on the importance of attractive brands and packaging, as well as online marketing. This service has helped provide assistance in making stickers, cardboard boxes and jars as a diversification of product packaging for UKM Kembang Goyang “Bu Ninik”, Sragen. This dedication also initiates the use of gift boxes as a respondent to the beautiful appearance of souvenirs. In UKM Kumari Crispi, this research carried out by initiating product innovations with various flavors that are of interest to millennialsand providing shelter assistance for Kumari Crispy souvenir shops to support online businesses that will be run. All of training and accompaniment hope can improve the business performance of the target SMEs by increasing the demand for their products.